As memórias pessoais de jovens e adultos como suporte de acolhimento na educação de migrantes e refugiados nos Centros Estaduais de Educação Continuada (CESEC) de Minas Gerais - Shirley Santos Oliveira (2024)
This thesis proposes a contemporary approach to promoting welcome in the education of migrants and refugees in State Continuing Education Centers (CESECs) in Minas Gerais. Inspired by the need to overcome obstacles when teaching text production, I chose to involve students in a didactic proposal focused on exploring the memoir genre, since I had been successful in working with this genre in another context in previous years. These reflections were triggered when I went to teach at a school that caters for young people, adults and elderly, many of whom are migrants and refugees who require specific language support. I then tried to develop a didactic proposal centered on memories, in order to contribute to the teaching of Portuguese as a Welcoming Language (PWL) in CESECs, involving migrant and refugee students in elementary school. The proposal aims to create a space for these students to share their life stories, languages and cultures through the interpretation and production of oral, written and multimodal texts, promoting the development of critical thinking. This initiative seeks to value cultural diversity in the classroom, improve students' communication skills and provide moments of listening and interactivity. Memoirs are presented as a tool for developing communication and reflection skills, allowing students to write, analyze and share memories critically and ratify cultural diversity. As a didactic support, we propose didactic material centered on personal memories and developed to meet the educational needs of migrants and refugees, through the exploration of autobiographical narratives, seeking to establish connections between the students' experiences, their adaptation to the new culture and language in order to promote self-expression, intercultural understanding and the construction of an inclusive learning environment. It is believed that this approach can be adapted and applied in similar educational contexts, offering a significant contribution to the promotion of inclusion, representativeness and cultural enrichment in classrooms.